Model Altman’s Z-Score dan Springate Memprediksi Financial Distress (Studi Kasus Perusahaan Sub Migas yang Tercatat di BEI Tahun 2017 - 2020) - nusyirwan, Nusyirwan; Kusdiana, Yayu; Tinaria, Lisa; Zubir, Zubir; Masril, Masril (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
The increase in the average need for oil and gas for both the public and the industrial sector has forced Indonesian oil and gas companies to look for new oil reserves in the midst of declining oil and gas production from year to year. If Indonesian sub-oil and gas companies cannot survive in these conditions, they are likely to experience losses that will affect their financial position and will eventually face financial distress or be threatened with bankruptcy. The purpose of this research is to determine the prediction of bankruptcy in sub-oil and gas companies in Indonesia that are listed on the IDX. 2017 – 2020 using Altman's Z – score and Springate models. Using the purposive sampling method in sampling, 11 oil and gas mining sub-sector companies were listed on the Indonesia Stock Exchange in 2017 – 2020 from a total population of 44 companies obtained from the website www.idx.co.id as secondary data. The score of each model is calculated mathematically with the Microsoft Excel Office 2019 application, and then performs calculations to find the most accurate bankruptcy prediction model. The results show that the Altman Z-Score and Springate models in predicting bankruptcy have a low level of accuracy.